Progressive Areas of Developing Transforming Factors of Tourism and Recreational Cluster of the Volgograd Region - Fetisova, Olga Vladimirovna; Kurchenkov, Vladimir Victorovich; Matina, Elena Sergeevna (International Journal of Economics and Financial Issues, 2016)
The goal of this article is to estimate the current state of transforming factors of the Volgograd Region as a basic driver of the development of tourism and recreational cluster of the region. In order to achieve the set goal, the work develops the methodology on scoring estimation of the region's resources state. This methodology is applied in the practical estimation of the current state of human, technical and technological, and natural factors of the tourism and recreational cluster of the Volgograd Region. Researching the state of transforming factors of the region, the authors revealed considerable problems, which restrain the formation and development of the tourism and recreational cluster of the Volgograd Region. They include problems related to provision of drinking water, deficit of professional personnel, and insufficient level of the development of the transportation infrastructure of the region. Systemizing the obtained results enabled the authors to define top-priority areas of the progressive development of the tourism and recreational cluster of the Volgograd Region. Keywords: tourism and recreational cluster (TRC), clustering, transforming factors, natural and recreational factor, tourism industry JEL Classifications: L83, R11, R49, O14, J24, Q59